Pregnancy outcome of isolated oligohydramnios in uncomplicated term pregnancies: an observational comparative study - Sebastian, Gisi; Shiyas, K. P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Oligohydramnios and its outcome is a relevant issue related to mother and fetus. Purpose of this study is to establish the obstetric and perinatal outcome in pregnancy associated with ‘isolated oligohydramnios as compared to women with normal liquor. Methods: This is an observational comparative study done at Al Azhar Medical College, Thodupuzha, Kerala, India on 50 pregnant women of 37 weeks of gestation or more and diagnosed to have oligohydramnios without any high-risk factors. Age, parity, gestational age matched patients without any high-risk factors and AFI >5 cm attending the OPD /ward were taken as controls. In each group there were 25 subjects. After getting informed consent those who fulfilled inclusion criteria were followed through the delivery and immediate neonatal outcome were assessed. Parameters like age, parity, amniotic fluid volume, gestational age at delivery, mode of onset of labor, indication of induction, methods of induction, need for augmentation of labor, CTG patterns, color of liquor, mode of delivery, indications of caesarean section., distribution of APGAR score were analyzed. Results: There were significant difference in maternal outcomes in patients with isolated oligohydramnios in the form of increased rates of induction of labor, augmentation of labor, meconium-stained liquor, non-reassuring fetal heart pattern, caesarean section rates without any significant effects on neonatal outcome. Conclusions: Isolated oligohydramnios has increased rate of induction of labor, meconium-stained liquor, CTG abnormalities and caesarean section rates without significant increase in neonatal morbidity and mortality.